Hubungan Kecanduan Gadget Dengan Emosi Dan Perilaku Remaja Usia 10-19 Tahun - Silvia Nur Rizki; Tati Suryati (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2022)
Emotion is a person's response to mental reactions that can be expressed with anger or fear, sadness and pleasure. Behavior is a collection of human behavior. These emotional and behavioral disorders can have an impact on teenagers who are addicted to gadgets, these behaviors can be irritable, forgetting time to pray, lack of socializing with the surrounding environment, lazy to do activities, and the teenager is restless and angry if the gadget is taken by his parents. This study aims to determine the relationship between gadget addiction and adolescent emotions and behavior in RW 06 Cipayung Ciputat, South Tangerang. This study uses a descriptive analytic design with a cross sectional approach. The total population in this study amounted to 132 people and the sample in this study amounted to 88 adolescents aged 10-19 years. The sampling technique used in this research is purposive sampling. The research instrument is a questionnaire sheet of emotional and behavioral disorders and Smartphone Addiction Scale Short Version (SSAV). The statistical test used is chi square with the results of the study there is a relationship between gadget addiction and adolescent emotions and behavior with p value = 0.013. Based on the results of this study, it is hoped that in the future the research results can be used as an illustration of gadget addiction with emotions and behavior in adolescents, further research is recommended to examine how to prevent gadget addiction with emotions and behavior using interventions to reduce gadget addiction which greatly affects adolescents emotions and behaviorAbstract is written with unstructured model and Should be written in English, is composed by one paragraph. Abstract is a brief description include background, aim, method, result, discussion, and conclusion.